Vznik a zánik narativu na příkladu putování jedné svatojánské sochy - Gausová Zörnerová, Markéta (Lidé města, 2023)
Using the example of the statue of St John of Nepomuk outside Saint John the Baptist Church (Na Prádle) in Prague’s Lesser Town, the author presents a reflection on the wide range of ideas upon which the narrative of a historical monument located in the city’s landscape depends on. This sculpture is especially admired as an example of Baroque art. The location of this statue in front of Saint John the Baptist Church is one of the factors that creates the impression of a picturesque and visually attractive spot. At the same time, however, this statue is known to have been originally located on the opposite shore of the Vltava River. Until the beginning of the 20th century, it was part of a religious cult, and its presence in the Cattle Market (now Charles Square) was seen as part of a greater pilgrimage site in which St John of Nepomuk was revered. By studying sources and literature, the author gradually uncovers layers of meanings intertwined with this particular work. At the same time, the author reflects on the possible consequences of transferring (not only) religious monuments from their original locations, especially with regard to the city’s memory.